Does Social Responsibility Influence Organizational Performance? - Ojeda-Hidalgo, José Felipe; López-Salazar, Alejandra; Álvarez-Orozco, Dolores Guadalupe (Estudios de Administración, 2019)
This research analyzes the impact of Corporate Social Responsibility (CSR) on business performance, specifically in the quality and image of products and services, customer satisfaction, market share, productivity, profitability and efficiency, and staff satisfaction. A sample of 671 companies of the State of Guanajuato, Mexico, was used to analyze the specific effects that the components of CSR have on financial and non-financial performance variables. The results show that efforts to respect and care for the environment, and ethical behavior with customers are key variables that positively influence the overall company performance. The implications for the business sector and future research are described.